A Stencil Printed, High Energy Density Silver Oxide Battery Using a Novel Photopolymerizable Poly(acrylic acid) Separator. (5th December 2014) - Braam, Kyle; Subramanian, Vivek
<x xml:space="preserve">Abstract</x> A novel photopolymerized poly(acrylic acid) separator is demonstrated in a printed, high‐energy‐density silver oxide battery. The printed battery demonstrates a high capacity of 5.4 mA h cm−2 at a discharge current density of 2.75 mA cm−2 (C/2 rate) while delivering good mechanical flexibility and robustness. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>